The Effect Of Hyperglycemia On Early Hospital Admission To The Incidence Of Mortality In Iscemic Stroke Patiens At Abdul Moeloek Regional General Hospital In 2017-2020 - Zahrani, Raisha Naomi; Ramayani, Fidha; Mayasari, Diana; Zanariah, Zam (CV. Jasa Sukses Abadi, 2024)
Stroke is the third leading cause of death in the world after coronary heart disease and cancer, both in developed and developing countries. Hyperglycemia can exacerbate neurological deficits and even increase mortality in ischemic stroke patients, but this is still controversial. This study aims to determine the effect of hyperglycemia at the beginning of hospital admission to the incidence of mortality in ischemic stroke patients at the Abdul Moeloek Regional General Hospital in 2017-2020. This type of research is analytic observational with a retrospective cohort study design. Data were taken from medical records with a total of 62 samples selected using a consecutive sampling technique. The results of the univariate analysis test showed that 53% of subjects experienced death (33 people). The results of the bivariate analysis test obtained p value <0.05 (p = 0.000), relative risk of 3.7, and a threshold value of 222.5 mg/dL. There is an effect of hyperglycemia at the beginning of hospital admission to the incidence of mortality in ischemic stroke patients at Abdul Moeloek Regional General Hospital.